Assessment of salient features of ground water resources - a case study in humid tropical region - BINEESH S; Nisha T. V; Preethi Abraham; Er. Asha Joseph (Guide) (Tavanur 2004 Department of Irrigation and Drainage Engineering)
Assessment of salient features of ground water resources - a case study in humid tropical region
Assessment of salient features of ground water resources - a case study in humid tropical region